2019
DOI: 10.35799/pha.8.2019.29257
|View full text |Cite
|
Sign up to set email alerts
|

FORMULASI DAN UJI EFEKTIVITAS KRIM ANTIBAKTERI EKSTRAK DAUN NANGKA (Artocarpus heterophyllus Lam.) TERHADAP BAKTERI Staphylococcus aureus

Abstract: Jackfruit leaves contain saponins, flavonoids and tannins. Which are know to have antibacterial compounds. The purpose of this study is to make cream of jackfruit leaf extract with a concentration of 5%, 10% and 15% and test the quality of preparations of  jackfruit leaf extract cream and  there is antibacterial effectiveness against Staphylococcus aureus bacteria. The method used is the ethanol extract of Jackfruit leaves by formulating it as an M/A type cream. The results showed the cream of  jackfruit leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…Based on research conducted by Kusumawati et al that there was a decrease in the number of Escherichia coli bacteria colonies after being given jackfruit leaf extract [7]. Another study conducted by Majid et al showed a decrease in the growth of Staphylococcus aureus bacteria after being given jackfruit leaf extract [14]. The results of this study are also in line with previous studies, namely jackfruit leaf extract has antibacterial properties against bacteria which is Porphyromonas gingivalis bacteria.…”
Section: Discussionsupporting
confidence: 90%
“…Based on research conducted by Kusumawati et al that there was a decrease in the number of Escherichia coli bacteria colonies after being given jackfruit leaf extract [7]. Another study conducted by Majid et al showed a decrease in the growth of Staphylococcus aureus bacteria after being given jackfruit leaf extract [14]. The results of this study are also in line with previous studies, namely jackfruit leaf extract has antibacterial properties against bacteria which is Porphyromonas gingivalis bacteria.…”
Section: Discussionsupporting
confidence: 90%
“…26 Akuades sebagai kelompok kontrol negatif tidak menunjukkan aktivitas antibakteri karena akuades bersifat steril tanpa kandungan aktif yang bersifat antibakteri dan tidak mengganggu senyawa utama. 27 Oleh karena itu, akuades sering dipakai sebagai kontrol negatif atau sebagai bahan campuran murni.…”
Section: Bahasanunclassified
“…Hasil pengamatan uji tipe emulsi selama 7 hari menujukkan sediaan krim yang mengandung ekstrak daun jelatang (Urtica dioica L.) dengan konsentrasi berbeda menunjukkan bahwa keempat formulasi tersebut termasuk dalam jenis krim M/A yang dilihat dari tersebarnya warna biru pada sediaan krim. Hal tersebut dikarenakan jumlah fase terdispersi (minyak/lemak) yang digunakan dalam pembuatan krim lebih sedikit daripada jumlah fase pendispersi (fase air), sehingga akan membentuk emulsi M/A dengan bantuan pengemulsi, hal ini dikarenakan fase minyak akan terdispersi merata dalam air (Majid et al, 2019). Hasil penelitian tipe emulsi yang telah dilakukuan sesuai dengan litelatur menurut Sembiring et al, (2022) bahwa tipe M/A ditunjukkan dengan warna biru yang terlihat pada fase luar karena kelarutan methylene blue dalam air.…”
Section: Uji Tipe Emulsiunclassified